Tourism consumer and microeconomic theory - Marsano Delgado, José Manuel Enrique (2017)
This paper analyzes and evaluates the microeconomic behavior of tourism, from the consumer ́s point ofview. In this sense, it tackles the definition of tourism consumer, the factors that determine it, analyzes theconsumer budget through the line of budget constraint, addresses the field of tourism consumer indifferencecurves explaining its point of equilibrium, to finally infer in the field of the budget restriction line from the pointof view of the changes and effects in the revenues and the prices of the tourism services.